Teaching Generation Text : Using Cell Phones to Enhance Learning - Nielsen, Lisa and Webb, Willyn H.; Foreword by Prensky, Marc (San Francisco Jossey-Bass, 2011)
Mobilizing the power of cell phones to maximize students' learning power Teaching Generation Text shows how teachers can turn cell phones into an educational opportunity instead of an annoying distraction. With a host of innovative ideas, activities, lessons, and strategies, Nielsen and Webb offer a unique way to use students' preferred method of communication in the classroom. Cell phones can remind students to study, serve as a way to take notes, provide instant, on-demand answers and research, be a great vehicle for home-school connection, and record and capture oral reports or responses to.
Include Index
Keywords: Mobile communication systems -- Telephone in education -- United States